Finance at the frontier : debt capacity and the role of credit in the private economy - Von Pischke, J. D. (Washington, D.C. : World Bank, 1991)
The purpose of this book is to suggest how good loans can be made to individuals and firms at the frontier. secondly to suggest how lending at the frontier can be remunerative to commercial banks, development banks and other development finance agencies that retail credit and assume credit risk.
Includes bibliographical references (p. 395-414) and index.
opc 27/09/16
Loans
Keywords: Finance - Developing countries; Economic development; Credit; Economic assistance- - Developing countries